2021
DOI: 10.21831/jpe.v9i2.36815
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service primary school mathematics teachers’ beliefs on mathematics assessment

Abstract: Assessment is an important component in learning mathematics. The practice of mathematics assessment is influenced by teachers' beliefs about the assessment. This study aims to explore the beliefs of primary school mathematics teachers regarding mathematics assessment. The research used quantitative research methods using survey methods to 71 prospective elementary school mathematics teachers. Confidence data regarding mathematics assessment was collected using closed and open questionnaires based on a framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Second, the use of questionnaires only captures the perspectives or beliefs of pre-service teachers. Various previous studies have shown that it is possible for a teacher to hold inappropriate or inconsistent beliefs (Op't Eynde, De Corte, & Verschaffel, 2002;Tamba, Cendana, & Adegbite, 2021;Tamba, Cendana, & Pratiwi, 2020;Tamba, 2021;Xenofontos, 2018).…”
Section: *P < 05mentioning
confidence: 99%
“…Second, the use of questionnaires only captures the perspectives or beliefs of pre-service teachers. Various previous studies have shown that it is possible for a teacher to hold inappropriate or inconsistent beliefs (Op't Eynde, De Corte, & Verschaffel, 2002;Tamba, Cendana, & Adegbite, 2021;Tamba, Cendana, & Pratiwi, 2020;Tamba, 2021;Xenofontos, 2018).…”
Section: *P < 05mentioning
confidence: 99%